Effect of creatine monohydrate supplementation for 3 weeks on testosterone conversion to dihydrotestosterone in young rugby players - Van der Merwe, Johann (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MPhil (Physiological Sciences))--University of Stellenbosch, 2006.